WOMEN, CASTE AND POLITICS IN COLONIAL INDIA - Aman Jyoti , Vinay Kumar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the social process of inclusion and exclusion of a community in India, it is generally designated with a particular political act while attaching privileges, rights, and disabilities within a framework of ideology. Many times, the caste ideology designated the Dalit at a particular place in the caste hierarchy and even resists them to attain their share of wealth and even social esteem. The British provided the Dalit reservation benefits which helped them to win their struggle against the designator. At the later stage, the Dalit initiated sub-caste identity movements while demanding respectable identity and equal share in different spheres in Indian in general and in the politics, particularly which has now become a significant sphere to study while emphasizing on identity politics about which the scholars, researchers, and even the policymakers have keen attention. It is not only a study of the Dalit identity but also in large perspective, is a study of women in the political set up, as she has also been deprived of various required just rights not provided to her in political sphere respectively.[1] [